Comparison of Ocular Wavefront Aberration Measurements Obtained Using Two Hartmann–Shack Wavefront Aberrometers. Issue 3 (20th March 2023) - Koh, Shizuka; Inoue, Ryota; Iwamoto, Yuuri; Mihashi, Toshifumi; Soma, Takeshi; Maeda, Naoyuki; Nishida, Kohji
Abstract : Objectives: To assess agreement between measurements of ocular wavefront aberrations obtained using the Pentacam AXL Wave (Oculus Optikgeräte GmbH) (Aberrometer A) and KR-1W (Topcon Corp) (Aberrometer B), both of which are based on the Hartmann–Shack principle. Methods: In this prospective case–control study, ocular wavefront aberrations measurements were obtained using both aberrometers in patients with keratoconus (KC) and control participants. Ocular wavefront aberrations were measured through the natural pupil without dilation using both devices in a dark room. For both aberrometers, accommodation was inhibited by automatically adding fogging. The individual Zernike coefficients from the second to fourth order were compared between the two aberrometers for a 4-mm pupil diameter. Results: Twenty-six KC and 29 control eyes were assessed. Statistically significant correlations ( P <0.05) were observed for all Zernike coefficients, except for Z4 −2 in the control group. Bland–Altman analysis indicated good agreement between aberrometers and no statistically significant differences in the control group. However, in the KC group, patterns of proportional error were observed in vertical coma Z3 −1 (r=0.338, P =0.008), trefoil Z4 −4 (r=0.701, P =0.003), secondary astigmatism Z4 −2 (r=0.348, P =0.025), and spherical aberrations Z4 0 (r=0.407, P =0.012). Conclusions: The Zernike coefficient values measured by the two aberrometers were well correlated in the control and KC groups. However, in eyes with KC, Aberrometer B tended to present greater values in several Zernike coefficients than Aberrometer A, suggesting that wavefront measurements obtained using the two aberrometers are not interchangeable in patients with KC.